Desain Perpustakaan Ideal di Era Modern - Widyastuti Widyastuti (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2017)
The development of the era also requires developments in various fields of life including libraries. Library likened as an information system that has three main elements of hardware, software and braindware. Hardware here is the Interior of the building, software is a service and braindware is a librarian. In this article the author seeks to explain ideas or ideas about the concept of an ideal library in terms of interior elements, services and librarians. This paper is expected to be one of the reference for library managers in the modern era. Perkembangan zaman menuntut pula perkembangan di berbagai bidang kehidupan termasuk perpustakaan. Perpustakaan diibaratkan sebagai sebuah sistem informasi yang memiliki tiga elemen pokok yaitu hardware, software dan braindware. Hardware disini adalah Interior gedung, software adalah layanan dan braindware adalah pustakawan.Dalam artikel ini penulis berupaya memaparkan ide atau gagasan mengenai konsep perpustakaan yang ideal ditinjau dari elemen interior, layanan dan pustakawannya. Tulisan ini diharapkan mampu menjadi salah satu referensi bagi para pengelola perpustakaan di era modern.